Nutrient recycling and utilization of Torreya grandis ‘Merrillii’ along an age gradient - Fan, Aifei; Jin, Songheng; Tan, Yangzhou; Huan, Weiwei; Chen, Wenjing; Wang, Xiaoyu; Han, Yini (Frontiers in Plant Science, 2025)
IntroductionThe intrinsic relationships among plants, litter, and soil nutrient characteristics, along with the responses of ecological stoichiometry to nutrient utilization, are critical for understanding the mechanisms of nutrient cycling. However, limited research in this area has constrained our comprehension of nutrient dynamics within ecosystems.MethodsTo investigate the stoichiometric characteristics and nutrient resorption traits of Torreya grandis plantations across various stand ages, as well as their adaptive strategies and nutrient utilization mechanisms under local growth conditions, we conducted a study in the T. grandis Forest Park. This study examined five stand age groups: young (20 years), near-mature (50 years), mature (80 years), over-mature (100 years), and thousand (1,000 years). We measured the nutrient contents of soil, fresh leaves, and litterfall, and analyzed their stoichiometric relationships and nutrient resorption characteristics.Results1.The growth of T. grandis plantations was primarily limited by nitrogen (N) during the early stages, transitioning to phosphorus (P) limitation with increasing stand age, particularly in the over-mature stage. High C:N and C:P ratios in leaves indicated low N and P use efficiency. 2.Leaf nutrient concentrations remained relatively stable across different stand ages, whereas nutrient concentrations in litterfall gradually declined, indicating an increase in nutrient cycling efficiency. Meanwhile, soil nutrient accumulation showed a gradual increase with stand development. T. grandis exhibited distinct nutrient resorption strategies at different stand ages: phosphorus resorption efficiency (PRE) was higher in young stands, whereas nitrogen resorption efficiency (NRE) significantly increased in mature and over-mature stands. Furthermore, this nutrient allocation mechanism influenced the nutritional content of T. grandis seeds, highlighting the significant impact of stand age on seed quality. 3.The nutrient characteristics of T. grandis plantations are influenced by both stand age and soil nutrient availability.Management practices should prioritize the supplementation of soil nutrients, particularly P, and the enhancement of nutrient cycling efficiency.DiscussionThis study offers a scientific foundation for the sustainable management and production of T. grandis plantations in the region, highlighting the importance of targeted soil nutrient management to improve ecosystem productivity and sustainability.